Prenatal Diagnosis of Aortopulmonary Window: A Case Report - Gupta, Ruchi; Singh, Aishwerya; Yadav, Priyanshi; Tiwari, Richa; Ahmad, Zohra (Journal of Fetal Medicine, 2025)
We report a rare case of a 31 year old female with no risk factors who came for a second opinion for a double outlet right ventricle transposition of great arteries type at 32 weeks of gestation. Fetal echocardiography was done, which showed abnormal communication between the main pulmonary artery and the ascending aorta. Diagnosis of aortopulmonary window was made, which was confirmed postnatally on echocardiography and computed tomography pulmonary angiography.
Keywords: fetal echocardiography; aortopulmonary window; red dot sign; ultrasound; right ventricular outflow tract